Synthesis and Investigation of Anti-Inflammatory Activity of New Thiourea Derivatives of Naproxen - Nikola Nedeljković; Vladimir Dobričić; Jelena Bošković; Marina Vesović; Jovana Bradić; Marijana Anđić; Aleksandar Kočović; Nevena Jeremić; Jovana Novaković; Vladimir Jakovljević; Zorica Vujić; Miloš Nikolić (MDPI AG, 2023)
The aim of the study was a synthesis and investigation of the dose-dependent anti-inflammatory effect of new thiourea derivatives of naproxen with selected aromatic amines and esters of aromatic amino acids. The results of the in vivo study indicate that derivatives of m-anisidine (4) and N-methyl tryptophan methyl ester (7) showed the most potent anti-inflammatory activity four hours after injection of carrageenan, with the percentage of inhibition of 54.01% and 54.12%, respectively. In vitro assays of COX-2 inhibition demonstrated that none of the tested compounds achieved 50% inhibition at concentrations lower than 100 µM. On the other hand, the aromatic amine derivatives (1-5) accomplished significant inhibition of 5-LOX, and the lowest IC50 value was observed for compound 4 (0.30 μM). High anti-edematous activity of compound 4 in the rat paw edema model, together with potent inhibition of 5-LOX, highlight this compound as a promising anti-inflammatory agent.